Do higher skill levels lead to better outcomes? The disproportionality between skills and outcomes for women - Heilmann, Lisanne; Gal, Iddo; Grotlüschen, Anke (My University, 2020)
This paper looks at men’s and women’s positions in the labour market and relates them to their basic skills. In a meritocratic society higher skills are supposed to relate to higher outcomes. We question whether this relation is equally true for men and women. Using data for 13 countries from the OECD Survey of Adult Skills (PIAAC), an international large-scale assessment, this paper examines monthly wages and a person’s probability to be in a managerial position. Our analyses show that, on average, men with higher skills get higher wages and have a higher probability to be in a managerial position than women with equally high skills. We show that the relation between skills and outcomes is more proportional for men than for women and that the gender pay gap does apply to women and men with similar skills. In addition, the results highlight a gap in managerial positions between men and women with the same basic skills.
Keywords: Arbeitsmarkt; basic skills; Einkommen; gender bias; income inequality; labour market discrimination; PIAAC; ddc:330